(3CaGSJGs (3GdeYQcI GdNGSQIs - (3YHO GdYRjR, YeQs; (3eMeO, HdGds; (3efJUQ, eQjes ([(3ecGf GdfTQ ZjQ eYQha(B]s (3GdafGQs, 2023)
(3haj Jdc GddMXI GfTbJ GdSeGA hXgQ Jfjf VNe GdMLe echf ef QGjf RQbGA fGQjI hcGfJ MQcGJg GdghGFjI JTcd ehLGJ gGFdI ef GdQYO hGdHQb CVGA gPG GdJfjf GdCQV HGddhf GdCRQbs
Keywords: (3GdCSGWjQs; (3GdbUU GdNQGajIs